Needs Analysis of Metacognitive Strategy Integration in Electronic Module Development to Improve Higher Order Thinking Skills - Faraniza, Zara; Suryawati, Evi; Syafrinal, Syafrinal (Journal of Educational Sciences, 2022)
This study aims to identify and explore metacognitive strategies that can be integrated into electronic modules to improve Higher Order Thinking Skills (HOTS). The initial research was conducted on 49 respondents from students majoring in Biology Education. The data collection instrument used a metacognitive test with 5 indicators: 1) Design what 2) elaboration; 3) Identify 4) Implement 5) Troubleshooting. The results of the metacognitive ability test show that in indicators 1 and 5 there are 53.06% and 40.81% who have metacognitive abilities. The results of the needs analysis are used as the basis for developing electronic modules by integrating metacognitive strategies in the form of analogies, mnemonics, and discrepant events. This research is Research and Development (R&D), this research develops a metacognitive-based e-module that refers to the ADDIE model, in this paper the data obtained from research up to the development stage. The results of the validity test by the validator showed that the metacognitive-based e-module obtained a score of 3.8 with a very valid category. The resulting e-module has the potential to improve students' higher-order thinking skills.